A prospective study of anti‐tumor necrosis factor therapy in South African rheumatoid arthritis patients. (12th February 2014) - Pettipher, Clive; Rudolph, Riana; Musenge, Eustasius; Tikly, Mohammed
Abstract: Objective: To quantify primary and secondary anti‐tumour necrosis factor inadequate response (aTNF‐IR) and intolerance in South Africans with rheumatoid arthritis (RA) over 1 year. Methods: Rheumatologists from nine independent private practices monitored RA patients commencing on aTNF therapy (incident cases) or already on aTNF therapy (prevalent cases). Observations at baseline and quarterly intervals recorded discontinuation of therapy for either lack of response or adverse effects. Results: Of the 98 patients screened, 86 were eligible to participate. Mean time from onset of symptoms of RA to start of aTNF treatment was 9.7 years (range: 0.5–32 years). Only 58 (67.4%) continued on aTNF therapy at 12 months, including five judged to have an aTNF‐IR. Overall 12 patients had a secondary aTNF‐IR with seven discontinuing for this reason. Seven patients discontinued due to adverse events, four due to funding problems and 10 were lost to follow‐up. Infections were the most common adverse events, but only two stopped treatment as a result. No cases of active tuberculosis (TB) were recorded, despite nine patients having a positive tuberculin skin test and one, a past history of pulmonary TB. Conclusions: Almost a third of patients discontinued aTNF therapy over the 1‐year period, with infections and inadequate response to treatment being the main reasons for discontinuation. The study highlights the need for biologics with alternative modes of action for patients with moderate to severe RA in South Africa.